2014
DOI: 10.1007/s10103-014-1574-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diode laser on direct pulp capping treatment

Abstract: At the present time, evidence-based, best practices have yet to be established for maintaining the vitality of teeth by managing caries-associated pulp exposure in permanent teeth. In terms of biomechanical and esthetic considerations, pulp capping has proven to be more effective than root-canal therapy. Given the low success rate of conventional methods, new techniques, such as laser-assisted repairs, should be developed. The purpose of this study was to compare the effectiveness of conventional and diode las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…The results of this study indicated that low level laser irradiation on exposure site could not compensate the limitation of gold foil as a pulp capping material. Most of the previous studies on the use of laser therapy in DPC employed high power lasers such as CO 2 and diode, [24][25][26][27][28][29] which have different mechanisms of action from low power lasers and so the results of those studies could not be compared with the present investigation. Regarding the effect of LLLT on DPC, Utsunomiya 14 reported that the use of a gallium-aluminum-arsenide diode laser (300 mW) on exposed surface of the pulp resulted in earlier expression of lectins and collagens in laser irradiation group than in the control group, and thus they concluded that laser therapy lead to the acceleration of wound healing process in the pulp.…”
Section: Low Level Laser Therapy On Direct Pulp Cappingmentioning
confidence: 99%
“…The results of this study indicated that low level laser irradiation on exposure site could not compensate the limitation of gold foil as a pulp capping material. Most of the previous studies on the use of laser therapy in DPC employed high power lasers such as CO 2 and diode, [24][25][26][27][28][29] which have different mechanisms of action from low power lasers and so the results of those studies could not be compared with the present investigation. Regarding the effect of LLLT on DPC, Utsunomiya 14 reported that the use of a gallium-aluminum-arsenide diode laser (300 mW) on exposed surface of the pulp resulted in earlier expression of lectins and collagens in laser irradiation group than in the control group, and thus they concluded that laser therapy lead to the acceleration of wound healing process in the pulp.…”
Section: Low Level Laser Therapy On Direct Pulp Cappingmentioning
confidence: 99%
“…On the other hand, a previous study used 980-nm diode laser with 3W until hemostasis was carried out before applying MTA and expressed less radiographic success in correlation to FC pulpotomy which suggest thermal damage to pulp cells (17) . The parameters used in this study regarding Diode laser output power and time of application in addition to remove the coronal pulpal tissue applying a hand instrument rather than laser and using proper water irrigationas well reflected the improvement in understanding laser method of application and prevented excessive heat generation which corporate previous studies (14,15) .…”
Section: Discussionmentioning
confidence: 70%
“…After initial hemostasis was gained, the 30 molars were managed by exhibiting root canal orifices to 810nm Diode Laser applied in continuous mode for 1-2 seconds using 400 microns optical fiber tip in contact mode with 1.5 watt power (14,15) .Pulp stumps were topped with MTA paste. Wet cotton pellet was located in pulp chamber, and cavity was topped with intermediate restorative material (IRM).…”
Section: • In Group Bmentioning
confidence: 99%
“…Several medicaments were reported for pulpal exposure with variable success, such as medical portland cement (PC), mineral trioxide aggregate (MTA), resin-modified glass ionomer (RMGI), calcium hydroxide (CH), antibiotics [5][6][7]. A few studies have shown that dental lasers have significant success in pulp healing after pulp exposure [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%